Soft Computing Under Uncertain Knowledge - García, Gustavo Santos; Buitrago, Rocio Santos (Journal of Advances in Applied & Computational Mathematics, 2022)
The early publications in the theory of fuzzy sets by Zadeh and Goguen show the intention to generalize the classical notion of a set and to accommodate the fuzziness that is contained in human language, namely human judgement, evaluation, and decisions. This article aims to show several approaches that allow effective treatment of uncertain, inaccurate, or unknown knowledge. On the one hand, a brief review of the theoretical background for these different paradigms is provided. On the other hand, the different extensions of soft sets are justified in the application to decision making. We pay special attention to applications in the medical sciences and provide a study case for biological signaling pathways.